Being-Together: Thinking through Technologically Mediated Sociality and Community - Willson, Michele (Taylor and Francis, 2012)
Our sociality is increasingly enacted through technology. This essay argues that the relationship between the technological mediation of social relations and the ways in which these practices are understood conceptually needs to be critiqued, rethought, and extended. Current approaches tend to accentuate the individual to the detriment of the social and often to understand technology instrumentally. Jean-Luc Nancy's notion of being singular plural and his understanding of the relations between singular beings and of ecotechnics are discussed briefly to illustrate an alternate direction for considering ways of being-together in Western techno-society.